Altered gray matter volume and functional connectivity in medial orbitofrontal cortex of bulimia nervosa patients: A combined VBM and FC study - Li, Wei-hua; Tang, Li-rong; Wang, Miao; Wang, Jia-ni; Guo, Ting; He, Qiong; He, Yu-yang; Lv, Zi-ling; Chen, Qian; Wang, Zheng; Li, Xiao-hong; Zhang, Peng; et al. (Frontiers in Psychiatry, 2022)
Brain structural and functional abnormalities have been shown to be involved in the neurobiological underpinnings of bulimia nervosa (BN), while the mechanisms underlying this dysregulation are unclear. The main goal of this investigation was to explore the presence of brain structural alterations and relevant functional changes in BN. We hypothesized that BN patients had regional gray matter volume abnormalities and corresponding resting-state functional connectivity (rsFC) changes compared with healthy controls. Thirty-one BN patients and twenty-eight matched healthy controls underwent both high-resolution T1-weighted magnetic resonance imaging (MRI) and resting-state functional MRI. Structural analysis was performed by voxel-based morphometry (VBM), with subsequent rsFC analysis applied by a seed-based, whole-brain voxelwise approach using the abnormal gray matter volume (GMV) region of interest as the seed. Compared with the controls, the BN patients showed increased GMV in the left medial orbitofrontal cortex (mOFC). The BN patients also exhibited significantly increased rsFC between the left mOFC and the right superior occipital gyrus (SOG) and decreased rsFC between the left mOFC and the left precentral gyrus, postcentral gyrus, and supplementary motor area (SMA). Furthermore, the z values of rsFC between the left mOFC and right SOG was positively correlated with the Dutch Eating Behavior Questionnaire-external eating scores. Findings from this investigation further suggest that the mOFC plays a crucial role in the neural pathophysiological underpinnings of BN, which may lead to sensorimotor and visual regions reorganization and be related to representations of body image and the drive behind eating behavior. These findings have important implications for understanding neural mechanisms in BN and developing strategies for prevention.